UPAYA PENINGKATAN PERSONAL HIGIENE MELALUI SOSIALISASI PEMBUATAN HAND SANITIZER BERBAHAN DASAR PIPER BETLE LINN - Anjarsari Anjarsari; Agustien Dwi Dayanty; Mariana Panji Ramadan (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
Since Covid-19 entered Indonesia in 2020, many problems have arisen, including health problems, economic problems, and education problems. The spread of covid-19 can be avoid implementing personal hygiene, One of them applying the 3M health protocol, using mask, washing hands with soap and keeping a distance. Partners are the people of Bojongkalong Village, Nyalindung District. The problems that faced by partners are the lack of public awareness how important personal hygiene, and not many public facilities that provide a place for washing hands. Hand sanitizer can be used as an alternative to washing hands with soap. used with the use of cases of transmission of covid-19, a lot of alcohol-based hand sanitizer. However, alcohol-based hand sanitizers cause irritation and burning, and they are not affordable. Betel leaf (piper betle linn) can be used as an alternative as a basic ingredient for herbal hand sanitizers, because it contains phenolic compounds and their derivatives so that they can inhibit the growth of microorganisms, and have antioxidants. The method are used by counselling about efforts to improve personal hygiene and simulating the manufacture of hand sanitizers from the basic ingredients of betel leaf (piper betle linn). The results of the service showed that the people of Bojongkalong Village are increasingly aware of the importance of personal hygiene, and know how to make hand sanitizer from betel leaf material (piper betle linn).